Analysis of Shooting Ability in Soccer Games of Class V Students of SDI Bontoala, Gowa Regency - Ricardo Valentino Latuheru (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
Shooting ability in football is one of the essential motor skills to be developed since elementary school age, because it is closely related to the game performance and psychomotor development of students. This study aims to analyze the level of shooting ability of grade V students of SDI Bontoala and identify their performance classification based on standardized measurement scores. The method used is a quantitative descriptive approach, with data collection techniques in the form of shooting skill tests given to 17 male students from a total population of 70 students. The data obtained were analyzed using descriptive statistics including average scores, frequency distributions, and classification of ability categories. The results showed that most students (35.3%) were in the